The effect of a minor health shock on labour market outcomes: The case of concussions - Florian Fouquet; Lisa Meehan; Gail Pacheco; Alice Theadom (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2023)
The literature on health shocks finds that minor injuries have only a short-term impact on labour market outcomes. However, mild traumatic brain injuries (mTBIs, commonly referred to as concussions) may be different as the medical literature highlights that they can have long-term health and cognitive effects. We use administrative data on all medically-diagnosed mTBIs in New Zealand linked to monthly tax records to examine the labour market effects of suffering a mTBI up to four years after the injury. We use a comparison group of those who suffer a mTBI but at a later date to overcome potential endogeneity issues, and employ a doubly-robust difference-in-differences method. We find that suffering a mTBI has negative effects on both employment and earnings. Rather than dissipating over time, these negative effects grow, representing a decrease in employment rate of 20 percentage points and earning losses of about a third after 48 months. Our results highlight the need for timely diagnosis and treatment to mitigate the effect of mTBIs on individuals' labour market outcomes to reduce economic and social costs.
Keywords: I10; I14; J01; J31; 330; health shock; mild traumatic brain injury; labour market outcomes